2022
DOI: 10.4103/ijstd.ijstd_72_21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiretroviral therapy on cardiac risk markers in people living with HIV/AIDS

Abstract: Introduction: Chronic HIV infection and antiretroviral therapy (ART) are the major causes of cardiovascular diseases (CVDs) and mortality in HIV patients. This study was conducted to look upon the effect of ART on CVD risk markers in patients on different ART regimens and ART-naïve patients. Methods: It was a cross-sectional, observational study done on 120 HIV-infected patients. CV risk markers were assessed and correlated with disease-specific factors within individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As such, increased resting heart rate and decreased short-term heart rate variability in HIV patients on cART are signs of parasympathetic dysfunction ( Lebech et al, 2007 ). On another note, Gupta et al (2022) ( Gupta et al, 2022 ) showed that patients on cART have greater levels of carotid intimal medial thickness and high-sensitivity C reactive protein than cART-naive participants which are major CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…As such, increased resting heart rate and decreased short-term heart rate variability in HIV patients on cART are signs of parasympathetic dysfunction ( Lebech et al, 2007 ). On another note, Gupta et al (2022) ( Gupta et al, 2022 ) showed that patients on cART have greater levels of carotid intimal medial thickness and high-sensitivity C reactive protein than cART-naive participants which are major CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%